A METHODOLOGICAL MODEL FOR INTEGRATING CHARACTER WITHIN CONTENT AND LANGUAGE INTEGRATED LEARNING IN SOCIOLOGY OF RELIGION - Alimi, Moh Yasir (Jurnal Komunitas: Research and Learning in Sociology and Anthropology, 2013)
AbstractIn this article, I describe a methodological model I used in a experimental study on how to integrate character within the practice of Content and Language Integrated Learning (CLIL) at the higher education Indonesia.This research can be added to research about character education and CLIL in tertiary education, giving nuances to the practice of CLIL so far predominantly a practice in primary and secondary schools.The research was conducted in Semarang State University, in the Department of Sociology and Anthropology, in Sociology of Religion bilingual class. The research indicates that the integration of character within CLIL enrich the perspective of CLIL by strengthening the use of CLIL for intellectual growth and moral development. On the other side, the use of CLIL with character education gives methods and perspectives to the practice of character education which so far only emphasise contents reforms without learning methods reforms. The research also reveals that the weakness of CLIL in using text for classroom learning can be overcome by the use of specific reading and writing strategies. I develop a practical text strategy which can be effectively used in highly conceptual subject such as sociology of religion.Â AbstrakArtikel ini bertujuan untuk mendeskripsikan model metodologis yang saya pakai untuk mengintegrasikannya karakter dalam Content and Language Integrated Learning (CLIL) pada pendidikan tinggi di Indonesia. Penelitian ini memperkaya penelitian mengenai pendidikan karakter dan penerapan CLIL di perguruan tinggi, selama ini penelitian semacam itu hanya biasa di level lebih rendah. Penelitian dilakukan di Universitas Negeri Semarang, pada kelas bilingual yang diikuti 25 mahasiswa, dan diujikan pada mata kuliah Sosiologi Agama. Pelajaran dari penelitian ini adalah integrasi karakter dalam CLIL dapat memperkaya CLIL. Sebaliknya penggunaan CLIL untuk mendidikkan karakter di kelas bilingual mampu menjawab berbagai tantangan pendidikan karakter di Indonesia yang sebagian besar masih berupa pengintegrasian karakter dalam kurikulum saja, tanpa disertai perubahan metode pembelajaran. Penelitian juga menunjukkan bahwa kelemahan CLIL dalam mengintegrasikan teksbook dalam pembelajaran kelas bilingual bisa diatasi dengan penggunaan strategi reading dan writing yang spesifik.Â© 2013 Universitas Negeri Semarang